Ciberespaço e dependência: uma análise dos vínculos do humano com o glocal interativo como habitus - Barbosa, Bárbara Conceição de Oliveira (2008)
The present Master s Degree Dissertation is intended to analyze the technological dependence its origins, its state-of-the-art and its consequences in the sphere of the relationship between human being and interactive media. The research contexts, of an exclusively theoretical nature, is the cyberculture, understood as a social organization of epoch, originated from the technological development that followed the Second World War. The main objective is to analyze the dependence phenomenon to which the cybercultural civilization is subject. The research problem lies in the following questionings: how a relationship so presented is configured? Which factors favor it? In the social-historic sphere, does dependence provides the preservation of technological lifestyles? Would it be present both in the collective plan and in the individual plan? As a main hypothesis, the study redefines and overvalues as dependence the strict social subjects bond to interactive technologies and networks, a bond whose analysis should consider the civilizatory and anthropological aspects involved, as it implies, simultaneously, recent history, society and individual. The research fundamentation privileges theoretical proposals articulated by the criticism category and consolidated in the last twenty years, based on the following authors: David Harvey, Fredric Jameson, Krishan Kumar and Jean-François Lyotard (post modernity); Paul Virilio (the concept of dromology); Eugênio Trivinho (cyberculture, cybercultural dromocracy and glocal phenomenon); Francisco Rüdiger and David Le Breton (cybercultural imaginary), Philippe Breton (communication as an utopian value); Pierre Bourdieu (concept of habitus); Vilém Flusser (technical image); Jean Baudrillard (the concept of excess). The reflection also incorporates references to researches who study the pathological use of Internet, such as Rosa Maria Farah and Denise Razzouk, among other authors and theoretical-epistemological perspectives. In relation to the achieved results, we can highlight, as favoring dependence, the context of cybercultural dromocracy (the velocity regime in the digital era), the glocal context (real-time living) and the inherent characteristics to interactive glocal, such as velocity, virtuality, deterritorialization, personalization, etc. This panorama gives cause to practices that, incorporated by the subject, are objectified in the glocalized habitus and affect it in body and in subjectivity. Such transformations and their consequences require gradual deepening in researches about the factors that endanger them, which justifies the present work. The research is inserted in the Culture and mediatic environments Research Line of PEPGCOS-PUC-SP, as it deals with the interactive technologies impact on the social-historic and cultural spheres; and finds support in the Communication area in Brazil, beside researches more and more concerned about cyberculture and its communicational practices